Lesbian mothers' lived psychological experience of planned motherhood in three South African cities : an exploratory study - Van Ewyk, Johanna Jacquetta (Stellenbosch : Stellenbosch University, 2013)
Thesis (MA)-- Stellenbosch University, 2013.